Behavioral response and pain perception to computer controlled local anesthetic delivery system and cartridge syringe - T D Yogesh Kumar; J Baby John; Sharath Asokan; P R Geetha Priya; R Punithavathy; V Praburajan (Wolters Kluwer Medknow Publications, 2015)
Aim: The present study evaluated and compared the pain perception, behavioral response, physiological parameters, and the role of topical anesthetic administration during local anesthetic administration with cartridge syringe and computer controlled local anesthetic delivery system (CCLAD). Design: A randomized controlled crossover study was carried out with 120 children aged 7-11 years. They were randomly divided into Group A: Receiving injection with CCLAD during first visit; Group B: Receiving injection with cartridge syringe during first visit. They were further subdivided into three subgroups based on the topical application used: (a) 20% benzocaine; (b) pressure with cotton applicator; (c) no topical application. Pulse rate and blood pressure were recorded before and during injection procedure. Objective evaluation of disruptive behavior and subjective evaluation of pain were done using face legs activity cry consolability scale and modified facial image scale, respectively. The washout period between the two visits was 1-week. Results: Injections with CCLAD produced significantly lesser pain response, disruptive behavior (P < 0.001), and pulse rate (P < 0.05) when compared to cartridge syringe injections. Application of benzocaine produced lesser pain response and disruptive behavior when compared to the other two subgroups, although the result was not significant. Conclusion: Usage of techniques which enhance behavioral response in children like injections with CCLAD can be considered as a possible step toward achieving a pain-free pediatric dental practice.